1993
DOI: 10.1111/j.1365-2842.1993.tb01513.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time of trimming on the surface finish of anterior composite resins

Abstract: This in vitro study investigates whether the surface smoothness of a finished composite resin is a function of the time at which it is trimmed. Five materials were studied. Visiodispers (VIS) is a sintered microfine, the remainder were hybrid formulations: Miradapt (MIR), Command Ultrafine (COM) and two experimental formulations-'EXP (2)' and 'EXP (15)'-with larger filler particles. All except MIR were photo-activated. Samples were placed and cured in holes machined in Perspex rods, ensuring excess of material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
0
14
0
2
Order By: Relevance
“…33 Although the surface obtained with Mylar strip is perfectly smooth, studies have shown that the outermost layer, which is rich with resin organic binder, has to be removed to produce a harder, wear resistant and esthetically stable surface. 11,16,20,31,34 Though both polishing systems tested in this study showed similar results in two composite systems, Ceram-X showed relatively lower values. The flexibility, hardness, and the granulations of the polishing system can influence the surface roughness of restorative materials.…”
Section: 32mentioning
confidence: 76%
See 1 more Smart Citation
“…33 Although the surface obtained with Mylar strip is perfectly smooth, studies have shown that the outermost layer, which is rich with resin organic binder, has to be removed to produce a harder, wear resistant and esthetically stable surface. 11,16,20,31,34 Though both polishing systems tested in this study showed similar results in two composite systems, Ceram-X showed relatively lower values. The flexibility, hardness, and the granulations of the polishing system can influence the surface roughness of restorative materials.…”
Section: 32mentioning
confidence: 76%
“…29,30 However, leaving resin surfaces as such is unacceptable due to the presence of the oxygen-inhibited layer, which will result in high water absorption and discoloration. 11,16,20,31 The surface roughness of composite resins is influenced by the size, hardness, and amount of filler material. 32 The surface roughness varied with the polishing systems and the type of composite used.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, superficial smoothness is one of the most important properties of a successful restoration~Joniot et al, Nagem Filho et al, 2003, Yazici et al, 2007!. Many studies~Lutz et al, 1983Heath et al, 1993;Nagem Filho et al, 2003;Roeder & Powers, 2004! have shown that polyester matrices provide smooth surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, finishing dental instruments become indispensable to improving restoration margins, removing overhangs, and producing appropriate contours~Lutz et al, 1983;Jung et al, 1997;Yap et al, 1998;Turssi et al, 2000;Ozgunaltay et al, 2003;Turkun & Turkun, 2004!. Carbide burs~Lutz et al, 1983Boghosian et al, 1987;Berastegui et al, 1992;Ferracane et al, 1992;Heath et al, 1993;Jung et al, 1997;Joniot et al, 2000;Reis et al, 2002!, diamond burs~Lutz et al, 1983Boghosian et al, 1987;Berastegui et al, 1992;Ferracane et al, 1992;Joniot et al, 2000;Lopes et al, 2002;Reis et al, 2002;Nagem Filho et al, 2003!, abrasive impregnated rubber cups and points ~Yap et al, 1998;Joniot et al, 2000;Turssi et al, 2000!, abrasive strips, stones~Lutz et al, 1983Bagheri et al, 2005!, polishing pastes~Yannikakis et al, 1998Turssi et al, 2000!, andabrasive discs~Lutz et al, 1983;Berastegui et al, 1992;Heath et al, 1993;Yannikakis et al, 1998;Joniot et al, 2000;Turssi et al, 2000;Lopes et al, 2002;Reis et al, 2002;Nagem Filho et al, 2003;Roeder & Powers, 2004! have been used for finishing and polishing...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation